2020
DOI: 10.1111/ctr.13900
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions in solid organ transplant candidates: A systematic review

Abstract: Solid organ transplantation (SOT) saves the lives of patients suffering from end-stage liver, heart, kidney, pancreas, and lung diseases 1,2 and improves disease-related symptoms as well as the quality of life (QoL) in these individuals. 3 Recent statistics show that close to 100 800 solid organ transplants are performed every year worldwide. 4 Many SOT candidates suffer from chronic disease for years before receiving a transplant, and depending on their health condition and which organ is involved, multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 79 publications
(293 reference statements)
0
15
0
Order By: Relevance
“…Whilst data were inadequate to perform a GRADE assessment, two reviews, comprising 23 individual studies, found no differences in intervention-attributable cardiopulmonary adverse events between prehabilitation and control arms (Supplementary Appendix 7). 51,52…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst data were inadequate to perform a GRADE assessment, two reviews, comprising 23 individual studies, found no differences in intervention-attributable cardiopulmonary adverse events between prehabilitation and control arms (Supplementary Appendix 7). 51,52…”
Section: Discussionmentioning
confidence: 99%
“…The majority of included reviews had critical weaknesses and were rated as critically low (26; 47%) 21e23,47,53e73 or low (16; 29%) 25,49,50,74e86 quality. Only four reviews were rated as high quality (7%), 51,52,87,88 seven (13%) were rated as moderate quality, 48,89e94 and two (4%) as unclear. 95,96 A full description is provided in Supplementary Appendix 8.…”
Section: Review Quality Assessmentmentioning
confidence: 99%
“…A systematic review of exercise pre-habilitation in the patients awaiting solid organ transplantation identified 23 studies. 27 Patient acceptance ranged from 16% to 100%. None of the studies reported any serious adverse effects of pre-habilitation, suggesting that this is a safe intervention even in those with advanced heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In the systematic review cited previously, patient acceptance ranged from 16% to 100%. 71 Cognitive impairment and depression, both common in the advanced heart failure population, may reduce patient acceptance and adherence to a structured prehabilitation program. While no studies have reported any adverse effects of prehabilitation, 71 there remains a reluctance among some exercise trainers and physiotherapists to supervise exercise programs in frail patients with advanced heart failure.…”
Section: Management Of Frailty In the Patient Referred For Heart Tran...mentioning
confidence: 99%